2011
DOI: 10.1186/1556-276x-6-176
|View full text |Cite
|
Sign up to set email alerts
|

Field emission enhancement of Au-Si nano-particle-decorated silicon nanowires

Abstract: Au-Si nano-particle-decorated silicon nanowire arrays have been fabricated by Au film deposition on silicon nanowire array substrates and then post-thermal annealing under hydrogen atmosphere. Field emission measurements illustrated that the turn-on fields of the non-annealed Au-coated SiNWs were 6.02 to 7.51 V/μm, higher than that of the as-grown silicon nanowires, which is about 5.01 V/μm. Meanwhile, after being annealed above 650°C, Au-Si nano-particles were synthesized on the top surface of the silicon nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…It is well known that FE properties of SiNNs strongly depend on the tip sharpness and aspect ratio of nanoneedles. Zhao et al showed that the FE properties are related to the composition, tip sharpness, aspect ratio, conductivity, and work function of SiNWs [26]. Therefore we conclude that sharper SiNNs have lower turn-on electric field.…”
Section: Resultsmentioning
confidence: 72%
“…It is well known that FE properties of SiNNs strongly depend on the tip sharpness and aspect ratio of nanoneedles. Zhao et al showed that the FE properties are related to the composition, tip sharpness, aspect ratio, conductivity, and work function of SiNWs [26]. Therefore we conclude that sharper SiNNs have lower turn-on electric field.…”
Section: Resultsmentioning
confidence: 72%
“…For instance, significant modification of the current saturation occurs after decoration of a bare silicon tip by a nanoparticle located on the tip apex . An additional enhancement of the electric field and a corresponding reduction of the FE threshold field can be achieved due to nanoparticle deposition on the tip . Furthermore, quantum confinement in nanoscale metallic particles may lead to unusual non‐monotonic current–voltage dependencies due to resonant tunneling or Coulomb blockade effect .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, quantum confinement in nanoscale metallic particles may lead to unusual non‐monotonic current–voltage dependencies due to resonant tunneling or Coulomb blockade effect . To obtain effective and controllable modification of FE characteristics, the nanoparticles preferably should be located at the apex of the emitter, but usually they are randomly distributed over the entire emitter surface, which also makes the interpretation of the experimental results controversial . Recently, we succeeded in deposition of single tungsten nanoparticles precisely on the apexes of the tips on a p‐type silicon wafer and performed preliminary study of their field emission properties .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations